Professional and practice characteristics associated with self-efficacy in assessment and intervention among social workers in aging. (27th May 2016) - Simons, Kelsey; An, Sofiya; Bonifas, Robin
ABSTRACT: This study examined professional and practice characteristics associated with assessment and intervention self-efficacy among gerontological social workers in Ontario, Canada who participated in online surveys. Results from multivariate analyses indicated that higher client acuity, longer duration of practice experience, smaller caseloads, and a greater proportion of clients 85 and over were significantly associated with greater assessment self-efficacy. Greater client acuity and smaller caseloads were also significantly associated with greater intervention self-efficacy. Implications for education include the importance of providing practical experience with the oldest old and with clients with greater biopsychosocial complexity. Also recommended is the need for manageable caseloads, especially when older adults with complex needs are part of the practice milieu.